Manufacture of a Simple One-Way Vibration Table and Earthquake-Safe Structure Model as Props in The Strengthening Structural Method - Wulandari, Galuh; Juliafad, Eka (Universitas Negeri Padang, 2024)
The problem raised is the absence of earthquake-safe structural props as learning support, so students still struggle to describe the behavior and effects of earthquakes on buildings. This research aims to produce earthquake-safe structural props media that are feasible to use as learning support media in the Structural Reinforcement Methods course. This research uses the Research and Development method, which adapts the DDD-E model, which consists of the Decide, Design, Develop, and Evaluate stages. The instrument used in this research is an assessment questionnaire for the media validation and practicality tests. Based on the product assessment of the earthquake-safe structure props media in the course of Structural Reinforcement Methods with the Aiken formula by media experts from all aspects obtained a V Aiken value of 0.87 with valid criteria, and the assessment by material experts from all elements received a V Aiken value of 0.96 with valid criteria. At the same time, students' practicality test of the earthquake-safe structure props media obtained a percentage value of 87% with very practical criteria. Therefore, the produced media can be declared very valid and applicable as learning support media.